Morphology controlled NH4V3O8 microcrystals by hydrothermal synthesis - Zakharova, Galina S.; Klingeler, Rüdiger (Dalton transactions, 2013)
Single crystalline ammonium trivanadate NH4V3O8 with variable morphologies, including shuttles, flowers, belts, and plates, was synthesized by the hydrothermal treatment of NH4VO3 with acetic acid. The crystals optimally grow under gentle conditions of 140 °C for 48 h. The resulting NH4V3O8 microcrystals were characterized by means of X-ray diffraction, scanning electron microscopy, infrared and Raman spectroscopy, static magnetization studies, and thermal analysis. The key factors to control the size and morphology of the crystals are the pH value and the vanadium concentration. A tentative microscopic growth mechanism is proposed and it is demonstrated how shape and morphology of the resulting microcrystalline material can be tuned by appropriate synthesis parameters.
Im Titel sind die Zahlen 4, 3 und 8 tiefgestellt
Gesehen am 26.07.2021